Research of approaches to increase the efficiency of functioning of railway transport subdivisions from the point of view of sustainable development - Kharchenko, O. I. (Science and Transport Progress, 2014)
Purpose. Modern transport systems are not stable and can not stand up to the destabilizing factors. Global track record in the economic and commercial management systems is the use of the concept of sustainable development. It is necessary on the basis of analysis of literary sources to define the directions of efficiency increase of functioning of railway transport subdivisions from the point of view of sustainable development. Methodology. To achieve the purpose the features of the use of sustainable development conception and its realization were investigated at a management of the complex systems. The existent models were also analyzed in the field of efficiency increase of functioning of railway transport subdivisions. Findings. On the basis of literary sources analysis, keeping up the conceptual essence of the sustainable development, the main directions of efficiency increase of subdivisions functioning were selected. They take into account the basic requirements of steady development and should be considered as a complex. Originality. New directions to consider the efficiency increase issues from position of sustainable development were offered by the author. Three components of conceptions of sustainable development (economic, ecological and social) should be examined in a balanced way. Thus, the above mentioned theoretical studies can promote the forming of new economy model corresponding to the purposes and principles of sustainable development. Practical value. The conducted analysis development confirms the necessity of researches on perspective directions of development of railway transport subdivisions, which are marked by the guidance of Ukrzaliznytsia. It enables to select basic directions for further research in the area of efficiency increase.